(Liquid + liquid) equilibria of four alcohol–water systems containing 1, 8-cineole at T = 298.15 K. (October 2016) - Li, Hengde; Feng, Zhangni; Wan, Li; Huang, Cheng; Zhang, Tianfei; Fang, Yanxiong
Graphical abstract: (Liquid + liquid) equilibria of C1 –C4 alcohol–water systems containing 1, 8-cineole are presented. Distribution ratios of alcohol in the mixtures are examined. The immiscible region of the LLE systems is evaluated and discussed. Highlights: Ternary (liquid + liquid) equilibria containing 1, 8-cineole are presented. Distribution ratios of C1 –C4 alcohol in the mixtures are examined. The LLE values were correlated using the NRTL and UNIQUAC models. Abstract: As an eco-friendly compound from essential oils, 1, 8-cineole (cineole, eucalyptol) has the potential to replace the ozone depleting industrial solvents. This paper presents experimental (liquid + liquid) equilibrium (LLE) data for four alcohol–water systems containing 1, 8-cineole. To evaluate the phase equilibrium properties of 1, 8-cineole in aqueous alcohol mixtures, LLE values for the ternary systems (water + methanol or ethanol or 1-propanol or 1-butanol + 1, 8-cineole) were determined with a tie-line method at T = 298.15 K under atmospheric pressure. The well-known Hand, Bachman and Othmer–Tobias equations were used to test the reliability of the experimental results. The binodal curves and distribution ratios of alcohol in the mixtures are shown and discussed. The experimental LLE values were satisfactorily correlated by the NRTL and UNIQUAC models.